PELATIHAN DALAM MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS VIII MTS AL-BUKHARY LABUHANBATU - Leli Hasanah Lubis; Dwina Putri; Yunita Sipahutar; Nani Rahmawati; Mulkan Darajat (JGK (Jurnal Guru Kita), 2023)
The aim of the training is to improve student learning outcomes, motivation and activeness in the writing aspect, namely writing observation reports. The way to improve students' poetry writing skills is with the training method, the problem is that class VIII students of MTs Al-Bukhary Labuhanbatu do not understand how to start writing good and correct poetry. The existence of contemporary poetry writing educational activities is a breath of fresh air for students of MTs Al-Bukhary Labuhanbatu as fans of literature. Talent. The poetry writing training was attended by 23 students who are lovers of literature and 3 Indonesian language teachers, and motivated and encouraged students to write poetry. As a result of the modern poetry writing training, 23 excellent poetry works were freely given to teachers and students so novice writers were not tied down.